INTEGRATION OF FORMAL DYNAMIC FEATURES IN THE PERSONALITY STRUCTURE OF STUDENTS REVEALING DIFFERENT LEVELS OF COMMUNICATION ACTIVITY - Tatyana V. Belykh; Anastasia M. Mairamyan (Вестник Северо-Кавказского федерального университета)
The article offers an analysis into the out comes obtained from an investigation into the relationships among the structural elements of the psychodynamic organization of individuality and the level of communication self-efficiency in students.